Effect of Educational Intervention on Road Safety Awareness and Practice among Medical Students in Chennai-A Cross-Sectional Study - Swetha NB; Sujitha P; Ashni Bhandari (Medsci Publications, 2021)
Background: Road transport is predisposing people to the risk of road accidents, injuries and fatalities. Road traffic injuries caused an estimated 1.24 million deaths worldwide, of which India alone accounted for 73%. This study was conducted to determine the improvement in the awareness of road safety measures post educational intervention. Methods: This was a Cross-sectional study with a follow-up component. The study was conducted among undergraduate medical students in Chennai. The sample size was calculated as 220. Study tool consisted of two questionnaires; one of which was given as pre-test and post-test and other 4 weeks after educational intervention to assess behaviour. Frequency and paired t test were used for analysis. Results: 46 (21%) did not have the habit of wearing helmet/seatbelt during every drive. 56 (25.5%) of them had used mobile phones while driving. Overall non-compliance to traffic rules was 25- 30%. 31 (14.1 %) faced road traffic accidents. The knowledge on road safety measures improved to 96% after educational intervention. Conclusion: An educational intervention presented in this study is effective to improve knowledge, attitude and behaviour about road safety among the study participants.